Dermatomycoses in Kuala Lumpur, Malaysia - Tzar, M.N.; Zetti, Z.R.; Ramliza, R.; Sharifah, A.S.; Leelavathi, M. (Universiti Kebangsaan Malaysia, 2014)
Prevalence of dermatomycoses varies from one centre to another due to many factors. Knowledge of local prevalence is useful to aid clinical diagnosis and treatment. Due to lack of data in Malaysia, this study aimed to look at the causes of dermatomycoses in Kuala Lumpur, Malaysia. Dermatological specimens including skin scrapings, hair and nail clippings were collected carefully from clinically suspected cases of dermatomycoses between 2008 and 2010. All cultures of skin, hair and nails that yielded positive fungal growth were included. Any fungal growth outside the streaking area, duplicate and incomplete data were excluded from the study. Three-hundred-fifty-eight patients were included. Male patients were slightly more than females with a ratio of 1.2:1. The median age was 53 years old with interquartile range of 38-64 years. More than half (53.6%) belonged to 20-60 years age group. Rates of culture isolation were 89.0% for nails, 56.2% for hair and 55.6% for skin. Five-hundred-twenty-two fungi were isolated from 358 clinical specimens. Non-dermatophyte moulds (NDMs) represented the largest group (50.5%; mainly Aspergillus species 18.7%), followed by yeasts (41.6%; mainly Candida species 26.8%) and dermatophytes (7.9%; mainly Trichophyton species 7.7%). In conclusion, NDMs and yeasts were more commonly isolated than dermatophytes from dermatological specimens in this centre. Current treatment regime that focuses on dermatophytes may be ineffective to treat dermatomycoses caused by NDMs or yeasts. Antifungal susceptibility study may be needed to guide therapy in recalcitrant cases.